Does the Presence of Risk Factors for Fetal Growth Restriction Increase the Probability of Antenatal Detection? A French National Study. Issue 1 (21st October 2015) - Monier, Isabelle; Blondel, Béatrice; Ego, Anne; Kaminski, Monique; Goffinet, François; Zeitlin, Jennifer
Abstract: Background: Screening for fetal growth restriction (FGR) is a major component of prenatal care. We investigated whether the presence of maternal and pregnancy risk factors for FGR improves the antenatal suspicion of FGR for infants born small‐for‐gestational age (SGA) as well as their impact on screening specificity. Methods: Data are from a representative sample of births from the 2010 French National Perinatal Survey ( n  = 14 100). Detection of FGR was determined by a suspicion of FGR noted in medical charts. Analyses were performed for singleton infants with birthweight under the 10th percentile (SGA), under the 3rd percentile (severely SGA), and above the 10th percentile (false positives) of French references. We studied risk factors for FGR (medical and obstetric conditions, advanced maternal age, nulliparity, body mass index and smoking) using multivariable Poisson regression to derive adjusted risk ratios (aRR). Results: Of SGA infants, 21.7% were suspected of FGR. The presence of obstetric and medical risk factors for FGR was associated with higher suspicion among SGA infants [RR 2.1, 95% confidence interval (CI) 1.7, 2.7]. However, despite the presence of these factors, 60% and 40% of SGA and severely SGA infants, respectively, were not suspected of FGR. Two per cent of normal birthweight infants were suspected of FGR, increasing to 5% when obstetric and medical risk factors were present. Smoking and older maternal age were unrelated to suspicion while females were more likely to be suspected of FGR. Conclusion: Our results suggest that better risk assessment could improve antenatal identification of FGR. Sex‐specific fetal growth references should be used to avoid systematic bias linked to sex.